The Phenomenon of Quiet Quitting. How Organizational Factors Affect Employee Productive Behavior - Made Virma Permana; Kris Brantas Abiprayu; Vini Wiratno Putri; Siti Ridloah; Altista Pradita Prismanti; Hanina Humaira; Fryza Naufal Laksmana (Management Analysis Journal, 2024)
This study aims to analyze  a model of productive behavior to overcome the phenomenon of quiet quitting. This study empirically examines the causes and implications of quiet quitting  behavior in higher education. This study examines whether the condition of employees from various generations has experienced changes in working methods and mindsets that cause the phenomenon of quiet quitting. In the long term, this phenomenon is suspected to reduce the behavior of extra roles in the organization. This study will use a quantitative approach to examine the factors that can encourage the emergence of quiet quitting  behavior in employees and its impact on performance. The number of samples used is 100-200 employees of public and private companies, with a distribution of varying range of positions and ages. The results of this test can help company leaders in Indonesia to identify quiet quitting  behavior and can be used to mitigate the negative effects caused.